Current practices for mental fatigue quantification and induction in movement science: Introducing the SPeCIFY guidelines - Schampheleer, E.; Habay, J.; Proost, M.; Arenales Arauz, Y. L.; Russell, S.; Roose, M.; Bian, C.; Meeusen, R.; De Pauw, K.; Roelands, B. (Sports Medicine, 2025)
Mental fatigue (MF) is a complex phenomenon with significant implications for human performance, for which there are numerous studies investigating the effects of MF. Nevertheless, there is considerable variability in the approaches used to induce and quantify MF, making it hard to compare findings across studies and draw well-supported conclusions. This review addresses the methodological variability in the induction and quantification methods of MF in movement science in the following ways: on the one hand, by providing an overview of task design strategies to induce MF, emphasizing the importance of tailoring task duration, difficulty, and nature to individual participants and specific research contexts; on the other hand, by providing an overview of current methods used to quantify MF, including behavioural, subjective, and physiological measures, and highlighting the strengths and limitations of each. Finally, this review proposes a best-practice framework for MF research, incorporating multi-method approaches for the induction and quantification of MF and introducing the Settings, Protocol establishments, Confounders, Individuals, Framework, and Yield (SPeCIFY) reporting guidelines that aim at improving consistency and transparency in future MF studies.